INTEGRATING DIGITAL ECONOMY MATERIALS INTO ENGLISH FOR SPECIFIC PURPOSES (ESP) INSTRUCTION: A STUDY OF ECONOMICS STUDENTS AT ITB AAS INDONESIA - Dewi Muliasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The rapid expansion of the digital economy has significantly reshaped the competencies required of economics graduates, particularly in understanding global business terminology, fintech systems, e-commerce practices, and digital financial communication. Despite this transformation, English for Specific Purposes (ESP) courses in higher education frequently remain centered on conventional business topics and do not systematically incorporate digital economy content. This study aims to investigate how digital economy materials are integrated into ESP instruction and how this integration supports the development of digital economic literacy among economics students at ITB AAS Indonesia. Employing a qualitative case study design, the research collected data through classroom observations, in-depth interviews with lecturers and students, and analysis of syllabi and instructional materials. The data were analyzed using thematic analysis to identify emerging patterns in instructional strategies, content adaptation, and student perceptions. The findings reveal that the inclusion of digital economy topics—such as fintech terminology, digital marketing discourse, online transaction communication, and startup pitching—enhances students’ understanding of contemporary economic concepts and strengthens their confidence in using English in digital business contexts. The study underscores the importance of contextualized ESP instruction that aligns with ongoing economic transformation and provides implications for curriculum development in higher education. Keywords: English for Specific Purposes (ESP); Digital Economy; Digital Economic Literacy; Economics Students; Higher Education; Qualitative Case Study